Réponses

2014-09-27T12:54:13+02:00
-2(2x-4)=6x-(3+x)
-2*(2x-4)=6x*3x
-2*(2x-4)=18x²
-2*2x=18x²+4
4x-18x²=4

si je me suis pas trompé ses sa
merci de m'aidé pour mon français svp
merci
2014-09-27T13:09:09+02:00
-8x+8=6x-3-x
-8x+8=5x-3
-8x-5x+8+3=0
-13x+11=0
-13x=-11
x=11/13
S={11/13}

4x-2+(5x-1)=-3(7-x)
9x-3=-21+3x
9x-3x-3+21=0
6x+18=0
6x=-18
x=-18/6
x=-3
S={3}

x/4+11=2x-3
x/4-2x+11+3=0
x/4-8x/4+14=0
7x/4=-14
x=-56/7
x=-8
S={-8}

4+3x/5=7x-1/8
4+3x/5-7x+1/8=0
3x/5-35x/5+32/8+1/8=0
-32x/5+33/8=0
-32x/5=-33/8
x=(-33 x 5)/(-32 x 8)
x=165/256